2021
DOI: 10.3390/ani11051215
|View full text |Cite
|
Sign up to set email alerts
|

Response of UK Horse, Pony and Donkey Owners to the Early Stages of the COVID-19 Pandemic

Abstract: In the UK, March 2020 was a time of great uncertainty as COVID-19 became increasingly widespread. The government responded by making suggestions about how people could reduce the risk of spread on 16 March, moved swiftly into closing schools on the 18 March before announcing a mandatory lockdown on the 23rd March. This was a challenging time for UK equestrians who had to balance maintaining their equine’s routine and daily care alongside the increasing biosecurity measures. A cross-sectional survey was distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Researchers in the United Kingdom surveyed equine owners in March of 2020 to understand the impact of the pandemic on their ability to interact and manage their equids ( Williams et al, 2020 ). Their findings showed differences by facility type where owners with equids kept in partial and full boarding situations experienced major impacts to the daily management of their equids, consistent with results by Hockenhull et al (2021) and Merkies et al, (2020) . Equine owners who kept their animals at home and those who pasture board felt the least disruption to daily management of their equids.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Researchers in the United Kingdom surveyed equine owners in March of 2020 to understand the impact of the pandemic on their ability to interact and manage their equids ( Williams et al, 2020 ). Their findings showed differences by facility type where owners with equids kept in partial and full boarding situations experienced major impacts to the daily management of their equids, consistent with results by Hockenhull et al (2021) and Merkies et al, (2020) . Equine owners who kept their animals at home and those who pasture board felt the least disruption to daily management of their equids.…”
Section: Resultssupporting
confidence: 65%
“…During early phase COVID restrictions, many facilities permitted access to animals for essential care ­reasons, but often nonessential care was restricted ( Greene et al, 2020 ). A survey administered by Hockenhull et al (2021) in the first few days of the emerging pandemic examined biosecurity practices and nonessential care at equine facilities in the United Kingdom. Findings showed that while some respondents stopped riding altogether, others took steps to minimize their risk of COVID-19 exposure through personal disease mitigation measures and limited unnecessary health risks while riding such as avoiding dangerous riding locations (e.g., loud or busy roads) or dangerous riding situation (e.g., jumping or riding young or nervous animals).…”
Section: Resultsmentioning
confidence: 99%
“…Owing to their status as business establishments, many livery yard owners made the decision to prevent non-essential workers from accessing the yard, including horse owners. Several studies have described disruption to horse and owner routine resulting from the closure of livery yards, as well as the negative consequences for the mental wellbeing of the owners that such restrictions may have had [ 9 , 10 , 11 , 13 ]. The decision by yard owners to close was often driven by the careful balancing of responsibilities toward the horses and humans who came into contact with the yard, as has been extensively documented by Furtado et al [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Focused evaluations on the impact of the pandemic upon distinct social cohorts can offer insights into the ways that social isolation, contagion and restricted living interact with sense of overall wellbeing within a community. Equestrian industry stakeholders form one such group which has received considerable attention from researchers seeking to understand the full impact of the pandemic upon human and animal welfare [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although these frameworks are yet to be widely adopted within the veterinary sector, evidence of their value in bringing about animal welfare-related human behaviour change is emerging. [4][5][6][7] One of the most widely used behavioural change frameworks in human health contexts is the COM-B model, which describes behaviour change in terms of three central components: capability (which includes access to information), opportunity (including the absence of barriers to behaviour change) and motivation (innate or external). 8 The model recognises that all three components need to be addressed when considering how best to design an intervention to promote behaviour change.…”
mentioning
confidence: 99%